2023
DOI: 10.3390/v15030665
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Influenza and Respiratory Syncytial Viruses in Suspected COVID-19 Patients: A Cross-Sectional and Meta-Analysis Study

Abstract: Non-SARS-CoV-2 respiratory viral infections, such as influenza virus (FluV) and human respiratory syncytial virus (RSV), have contributed considerably to the burden of infectious diseases in the non-COVID-19 era. While the rates of co-infection in SARS-CoV-2-positive group (SCPG) patients have been determined, the burden of other respiratory viruses in the SARS-CoV-2-negative group (SCNG) remains unclear. Here, we conducted a cross-sectional study (São José do Rio Preto county, Brazil), and we collected our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…The results of this study revealed a higher admission to the Emergency Department of Nikaia hospital for female patients (54%) with common upper respiratory tract clinical manifestations, than male (46%). Similar results are described in the literature [17]- [20], [28]. However, there are studies conducted in India,which conclude the opposite results about hospital admission regarding gender [21], [22].…”
Section: Resultssupporting
confidence: 87%
“…The results of this study revealed a higher admission to the Emergency Department of Nikaia hospital for female patients (54%) with common upper respiratory tract clinical manifestations, than male (46%). Similar results are described in the literature [17]- [20], [28]. However, there are studies conducted in India,which conclude the opposite results about hospital admission regarding gender [21], [22].…”
Section: Resultssupporting
confidence: 87%